Development of a cardiovascular magnetic resonance‐compatible large animal isolated heart model for direct comparison of beating and arrested hearts. (12th February 2022) - Scott, Andrew D.; Jackson, Tim; Khalique, Zohya; Gorodezky, Margarita; Pardoe, Ben; Begum, Lale; Bruno, V. Domenico; Chowdhury, Rasheda A.; Ferreira, Pedro F.; Nielles‐Vallespin, Sonia; Roehl, Malte; McCarthy, Karen P.; et al.
Abstract : Cardiac motion results in image artefacts and quantification errors in many cardiovascular magnetic resonance (CMR) techniques, including microstructural assessment using diffusion tensor cardiovascular magnetic resonance (DT‐CMR). Here, we develop a CMR‐compatible isolated perfused porcine heart model that allows comparison of data obtained in beating and arrested states. Ten porcine hearts (8/10 for protocol optimisation) were harvested using a donor heart retrieval protocol and transported to the remote CMR facility. Langendorff perfusion in a 3D‐printed chamber and perfusion circuit re‐established contraction. Hearts were imaged using cine, parametric mapping and STEAM DT‐CMR at cardiac phases with the minimum and maximum wall thickness. High potassium and lithium perfusates were then used to arrest the heart in a slack and contracted state, respectively. Imaging was repeated in both arrested states. After imaging, tissue was removed for subsequent histology in a location matched to the DT‐CMR data using fiducial markers. Regular sustained contraction was successfully established in six out of 10 hearts, including the final five hearts. Imaging was performed in four hearts and one underwent the full protocol, including colocalised histology. The image quality was good and there was good agreement between DT‐CMR data in equivalent beating and arrested states. Despite the use of autologous blood and dextran within the perfusate, T2 mapping results, DT‐CMR measures and an increase in mass were consistent with development of myocardial oedema, resulting in failure to achieve a true diastolic‐like state. A contiguous stack of 313 5‐μm histological sections at and a 100‐μm thick section showing cell morphology on 3D fluorescent confocal microscopy colocalised to DT‐CMR data were obtained. A CMR‐compatible isolated perfused beating heart setup for large animal hearts allows direct comparisons of beating and arrested heart data with subsequent colocalised histology, without the need for onsite preclinical facilities. Abstract : A cardiovascular magnetic resonance (CMR)‐compatible isolated perfused beating porcine heart model was developed that allows direct comparison of data acquired in multiple states of contraction between the beating and arrested heart. We describe the development of this model, its successes and failures, including the presence of oedema in the hearts. In this study, microstructural measures were obtained from the porcine hearts using diffusion tensor CMR in the most and least contracted states with subsequent colocalised histology.